Photocatalytic degradation of methylene blue with silver doped ZnO nanoparticles grown on microscopic sand particles (Degradasi metilena biru menggunakan nanopartikel ZnO sebagai fotomangkin yang didopkan dengan perak tumbuh di atas pasir bersaiz mikro) - Safian, Nur Azmina Mohamed; Nor, R.M.; Rafaie, Hartini Ahmad; Abdul Sani, Siti Fairus; Osman, Zurina (Malaysian Analytical Sciences Society, 2018)
Pure and Ag doped ZnO nanoparticles were synthesized on microscopic sand particles by sol-gel method. Silver nitrate was used as the doping precursor, Ag doping levels of 1.3 to 7.7 of Ag/Zn ratios were obtained based on energy dispersive X-ray spectroscopy analysis. X-ray diffraction results show that a ZnO (101) peak of Ag doped samples are shifted towards lower degree which around 0.17o compared to pure ZnO NPs, indicating the existence of doping in the Ag doped samples. The pure and Ag doped ZnO samples were used as photocatalysts in the degradation of methylene blue under UV irradiation. Photodegradation efficiency based on the pseudo-first kinetics model gave measured values of the photodegradation rate, k of 8.9, 11.8, 12.7, 14.8 and 17.4 x 10-3 min-1 for pure, 1.3, 1.6, 1.7 and 2.4 of Ag/Zn ratios, respectively. At higher doping levels of 3.3 and 7.7 of Ag/Zn ratios, the k values receded to 12.7 and 12.0 x 10-3 min-1, respectively. The increasing trend on k values can be due to the doping defect levels which trapped the recombining electrons, thus lengthening the lifetime of the electron hole pairs.